The Ebola Virus Disease Outbreak in West Africa: A Wake-up Call to Revitalize Implementation of the International Health Regulations - Olu, Olushayo Oluseun (Frontiers in Public Health, 2016)
The 2014/15 Ebola virus disease (EVD) outbreak in West Africa has highlighted the inherent weaknesses associated with the implementation of the International Health Regulations (IHR). In this perspective article, the lessons learnt from the outbreak are used to review the challenges impeding effective implementation of the IHR and to propose policy and strategic options for enhancing its application. While some progress has been achieved in implementing the IHR in several countries, numerous challenges continue to impede its effectiveness, especially in developing countries, such as those affected by the West Africa EVD outbreak. Political and economic sensitivities associated with reporting public health emergencies of international concern (PHEIC), inadequate resources (human and financial), and lack of technical know-how required for implementation of the IHR are weaknesses that continue to constrain the implementation of the regulations. In view of the complex sociopolitical, cultural, and public health dimensions of PHEICs, frameworks, such as the IHR, which have legal backing, seem to be the most effective and sustainable option for assuring timely detection, notification, and response to such events. Renewed efforts to strengthen national and global institutional frameworks for implementation of the IHR are therefore required. Improvements in transparency, commitment, and accountability of parties to the IHR, mainstreaming of the IHR into national public health governance structures, use of multidisciplinary approaches, and mobilization of the required resources for the implementation of the IHR are imperative.